Re-estimation of the vertical sensible heat flux by determining the environmental temperature on a single-point tower measurement - Qi, Yongfeng; Shang, Xiaodong; Chen, Guiying; Gao, Zhiqiu; Bi, Xueyan; Yu, Linghui; Mao, Huabin (Frontiers in Earth Science, 2024)
Surface energy balance has always been a goal of those studying the Earth's climate system. However, a multitude of studies have demonstrated that turbulent heat fluxes are usually underestimated by eddy covariance (EC) measurements, such that the energy balance is not closed. In this study, a new perspective on the calculation of sensible heat flux based on the environmental temperature is proposed using EC. With the proposed approach, additional sensible heat fluxes were detected as outcomes of the vertical transportation of thermal structures in the atmospheric surface layer (ASL).For the data obtained over a 40-day period, over a grassland in Southern China, additional sensible heat flux observations exceeding 50 W m -2 were measured for 8 of the 40 days; smaller but still significant contributions were captured for another 11 days. In the proposed model, the difference between the mean and environmental temperature (∆) and the local mean vertical velocity ( ) serve as determinants for the additional flux, where the former can be deemed as the activity level of the thermal structures. A modeled underestimation of α[ ] of the total vertical sensible heat flux was revealed using our method, where α equals to 3.55 for this study, is the traditional EC results and [ ] is the non-dimensional . Moreover, the additional flux usually showed large values in the daytime that were not detectable using the traditional EC method; thus, this may explain the energy